Policies for promoting walking and cycling in England : a view from the street - Pooley, C; Horton, D; Scheldeman, G; Mullen, C; Jones, T; Tight, M; Jopson, A; Chisholm, A (Elsevier, 2013)
Transport policies to increase active and sustainable travel in Britain have focused mainly on persuading people of the health benefits of walking and cycling for short trips and have assumed that if people can be persuaded that more active travel has personal benefits then behavioural change will follow. Research reported in this paper, based mainly on detailed qualitative research in four English towns, argues that the complexities and contingencies that most people encounter in everyday life often make such behavioural change difficult. Attention is focused on three sets of factors: perceptions of risk; constraints created by family and household responsibilities; and perceptions of normality. It is suggested that unless such factors are tackled directly then policies to increase levels of walking and cycling will have limited success. In particular, it is argued that there needs to be a much more integrated approach to transport policy that combines interventions to make walking and (especially) cycling as risk-free as possible with restrictions on car use and attitudinal shifts in the ways in which motorists view other road users. Such policies also need to be linked to wider social and economic change which, in combination, creates an environment in which walking or cycling for short trips in urban areas is perceived as the logical and normal means of travel and using the car is viewed as exceptional.